Design, Development and Implementation Sop With Service Blueprint, K Pharmacy in Surabaya - Yessica Anggraini Sutanto; Erna Andajani (DINASTI RESEARCH, 2020)
Background of this study is due to the absence Standard Operation Procedure (SOP) in K Pharmacy, can operational chaos. Solving these problems can be done by using the service blueprint, to find out the error process. This research not only designed, but also developed and implemented Standard Operation Procedure (SOP) and Service Blueprint. This type of research is applied research with descriptive qualitative methods. The technique of collecting data this study using purposive sampling technique. The methods collection data of this study were observation and depth interview. This research design used iterative process (exploration, creation, reflection and implementation). The result of this study are need to implement an electronic medical record system when doing assessments, implementing an inventory management system, providing a queue serial number of customers, and implementing an electronic cash register system